INEQUALITY EXPERIENCED BY WOMEN AS REFLECTED IN LOUISA MAY ALCOTT’S 'LITTLE WOMEN' - Fatimah Pungkasari; Wajiran Wajiran (UIN Raden Mas Said Surakarta, 2024)
This study explores women's roles and societal expectations in the 19th century, mainly as portrayed in Little Women by Louisa May Alcott. The analysis focuses on three main areas: family, education, and societal roles. In family life, women were largely confined to domestic roles, with ideals such as ‘the angel in the house’, which glorified self-sacrificial wives and mothers. Jo March, the main character in the novel, however, challenges this norm by assuming the responsibilities of the ‘man of the family’ in her father’s absence. In education, women’s access was limited, reflecting broader inequalities. Mrs. March, or Marmee, becomes a pivotal moral teacher to her daughters, instilling values that transcend material wealth. Despite societal constraints, Jo and her sisters navigate personal and financial challenges, with Jo ultimately breaking traditional gender norms by pursuing a career as a writer. This study further reveals how women’s opportunities were shaped by class and how marriage was often seen as the only path to social mobility. Overall, this paper highlights how Little Women reflects the limitations and opportunities for women in the 19th century, challenging prevailing gender stereotypes through its portrayal of women’s independence, ambition, and resilience.